2018
DOI: 10.1186/s12871-018-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of isoflurane exposure in pregnant rats on the learning and memory of offsprings

Abstract: BackgroundAbout 2% of pregnant women receive non-obstetric surgery under general anesthesia each year. During pregnancy, general anesthetics may affect brain development of the fetus. This study aimed to investigate safe dosage range of isoflurane.MethodsForty-eight SpragueDawley (SD) pregnant rats were randomly divided into 3 groups and inhaled 1.3% isoflurane (the Iso1 group), 2.0% isoflurane (the Iso2 group) and 50% O2 alone (the control group) for 3 h, respectively. Their offsprings were subjected to Morri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…The results of this study, and those from the literature, highlight the need for caution when using isoflurane which, when used repeatedly, is not benign as is often assumed (Bajwa et al 2018;Crystal et al 2012;Huang et al 2018;Li et al 2018;Lin and Zuo 2011;Ni et al 2017;Paasonen et al 2018;Wu et al 2015;Zhang et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…The results of this study, and those from the literature, highlight the need for caution when using isoflurane which, when used repeatedly, is not benign as is often assumed (Bajwa et al 2018;Crystal et al 2012;Huang et al 2018;Li et al 2018;Lin and Zuo 2011;Ni et al 2017;Paasonen et al 2018;Wu et al 2015;Zhang et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…The prenatal period is critical for brain development, and, at this epoch, the embryo is especially vulnerable to environmental interference. Clinical and preclinical studies have documented that maternal anesthetics exposure can result in abnormal brain development in offspring (Huang et al., 2018 ; Reitman & Flood, 2011). Concurrently, pregnant women can also suffer from sleep disorders owing to alterations in physiology and anatomy that occur during pregnancy (Bacaro et al., 2020 ; Miller et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have also shown that isoflurane exposure during pregnancy can lead to offspring cognitive dysfunction (Fan et al., 2022 ). Rodent studies have documented that fetal exposure to general anesthesia induces long‐term neurobehavioral dysfunctions, such as cognitive impairment (Huang et al., 2018 ; Zuo, Li et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…34 Other anaesthetic agents, such as isoflurane or tribromoethanol, have been proposed as safer alternative anaesthetic agents with regard to embryo development in survival rodent toxicity models. 33,35,36 For procedures lasting more than around 10 minutes, provision of an external form of heat or wrapping of the animal or its extremities with an insulator, such as a plastic wrap, is advised in order to maintain normal core body temperature. 32,35…”
Section: Discussionmentioning
confidence: 99%